Modifier's influence on spectral properties of dysprosium ions doped lead boro-telluro-phosphate glasses for white light applications. (December 2022) - Komal Poojha, M.K.; Vijayakumar, M.; Matheswaran, P.; Sayed Yousef, El; Marimuthu, K.
Highlights: New glass network of Dy 3+ doped lead boro-telluro-phosphate glasses have been studied. Influence of Li +, Zn 2+, Ca 2+, Sr 2+, and Ba 2+ on Dy 3+ emission properties are reported. The structural and optical studies were investigated for all the glasses. Generation of cool white light is confirmed using CCT values. Abstract: Trivalent dysprosium doped Lead boro-telluro-phosphate glasses were synthesized with varying modifiers such as Li +, Zn 2+, Ca 2+, Sr 2+, and Ba 2+ using traditional route of glass preparation (melt quenching). The basic network formation and spectroscopical aspects of the as piped outed glasses was analyzed using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), UV–vis-NIR, photoluminescence (PL) and emission decay measurements. The existence of elementary functional groups pertaining to the present glass network was explored through FTIR spectral analysis. Bonding parameters (δ) were found to analyze the bonding nature of the rare earth ions and the surrounding metal ligand site. The optical bandgap, band tailing parameter and Urbach energy was found using Tauc's method in order to identify the transparent region of the prepared glass samples. Furthermore, the symmetry of ligands around the Dy 3+ ions has been explored with absorption spectral data by inspecting the Judd-Ofelt (JO) parameters and oscillator strengths of the as-synthesized samples. The radiative properties for instance branching ratios (βR ), stimulated emission cross-section (σP ) and lifetime (τR ) of the meta stable states are estimated to realize the novel applications. The CIE colour coordinates and Y/B ratio values were estimated employing the photoluminescence spectra, whereas the colour purity and it's colour correlated temperature (CCT) were determined following the (x, y) values thus confirms the generation of neutral white light emitting ability of the prepped samples. The decay or lifetime analysis shows the well fitted non-exponential behavior of the present Dy 3+ doped Lead boro-telluro-phosphate glasses.